Ceramic lasers - Ikesue, Akio, 1958- (Cambridge University Press, 2013)
Co-authored by one of the pioneers in the field, this book describes the fabrication technology and theoretical characterization of ceramic material properties. It describes novel types of solid lasers and other optics using ceramic materials.